2023
DOI: 10.1111/dom.14950
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic steatosis and advanced hepatic fibrosis are independent predictors of long‐term mortality in acute myocardial infarction

Abstract: Aim To examine the prevalence and prognosis of hepatic steatosis and fibrosis in post‐acute myocardial infarction (AMI) patients. Methods Patients presenting with AMI to a tertiary hospital were examined from 2014 to 2021. Hepatic steatosis and advanced hepatic fibrosis were determined using the Hepatic Steatosis Index and fibrosis‐4 index, respectively. The primary outcome was all‐cause mortality. Cox regression models identified determinants of mortality after adjustments and Kaplan–Meier curves were constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…Moreover, this risk is independent of other cardiovascular risk factors or amount of cardiac arterial stenosis [85]. There is also an association between hypertension and steatosis [86], and steatosis is a predictor of mortality in acute myocardial infarction with hepatic fibrosis having only a slightly increased risk of mortality compared to steatosis [87]. Finally, steatosis more than 30% predicts graft failure when steatotic livers are transplanted [88].…”
Section: Ld Effects On Hepatic Morphology In Mashmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this risk is independent of other cardiovascular risk factors or amount of cardiac arterial stenosis [85]. There is also an association between hypertension and steatosis [86], and steatosis is a predictor of mortality in acute myocardial infarction with hepatic fibrosis having only a slightly increased risk of mortality compared to steatosis [87]. Finally, steatosis more than 30% predicts graft failure when steatotic livers are transplanted [88].…”
Section: Ld Effects On Hepatic Morphology In Mashmentioning
confidence: 99%
“…84 There is also an association between hypertension and steatosis, 85 and steatosis is a predictor of mortality in acute myocardial infarction with hepatic fibrosis having only a slightly increased risk of mortality compared with steatosis. 86 Finally, steatosis more than 30% predicts graft failure when steatotic livers are transplanted. 87 While the specific mechanisms of this graft failure have not been fully established, it is likely that the aforementioned effects of LD accumulation on the hepatic microenvironment and tissue oxygenation impact graft suitability.…”
Section: Metabolic Dysfunction-associated Steatotic Liver Disease (Fo...mentioning
confidence: 99%
“…[8][9][10][11][12][13] Prior studies have shown that individuals at high risk of liver fibrosis according to non-invasive scores exhibit a high risk of CVD. [14][15][16][17] Comparisons among the most common non-invasive scoring systems and HFS have shown that, in cross-sectional analysis carried out in patients with biopsy-proven NAFLD, HFS has the best diagnostic performance for the identification of significant and advanced liver fibrosis, while having a moderate diagnostic accuracy at identifying patients at risk of incident CVD. 17 Accordingly, HFS was shown to have the best diagnostic performance for the identification of advanced liver fibrosis in another study carried out in patients with NAFLD or viral chronic liver disease.…”
Section: Introductionmentioning
confidence: 99%
“…4 As EAT has metabolic, thermogenic, and mechanical cardioprotective characteristics, 4 this fat deposit has been implicated in the progression of subclinical atherosclerosis and coronary artery disease. 5–10…”
mentioning
confidence: 99%
“…4 As EAT has metabolic, thermogenic, and mechanical cardioprotective characteristics, 4 this fat deposit has been implicated in the progression of subclinical atherosclerosis and coronary artery disease. [5][6][7][8][9][10] Previous studies have examined the associations between EAT and heart failure, coronary artery disease, 11 and major adverse cardiovascular events (MACE). 4 Mancio and colleagues assessed the computed tomography (CT)-derived EAT volume and its relationship with coronary artery disease, and the association of EAT with increased risk of significant stenosis and MACE.…”
mentioning
confidence: 99%